Role of CD133 in colorectal cancer - Ahmed, Tarek Mohamed Abdel Moneim Mohamed Elsaba (2011)
CD133 is a pentaspan transmembrane glycoprotein of ~120 kDa, which was initially used to identify haematopoietic stem cells and, later on, used for the isolation and study of cancer stem cells in many different types of solid tumour including colorectal cancer. Although CD133 expressing cells are thought to represent cancer stem cells, little is known about the exact role of CD133 and the molecular mechanisms underlying control of CD133 expression. This project sought to investigate these questions in colorectal cancer.